Efficacy and Safety of the Early Addition of Vasopressin to Norepinephrine in Septic Shock. (November 2019) - Hammond, Drayton A.; Cullen, Julia; Painter, Jacob T.; McCain, Kelsey; Clem, Oktawia A.; Brotherton, Amy L.; Chopra, Divyan; Meena, Nikhil
Background: Delays in achievement of target mean arterial pressure (MAP) have been associated with increased mortality in patients with septic shock. Vasopressin may be added to norepinephrine to raise MAP or decrease norepinephrine dosage. The purpose of this study was to determine whether early initiation of vasopressin to norepinephrine resulted in a reduced time to target MAP compared to norepinephrine monotherapy. Methods: This retrospective cohort study compared early addition of vasopressin within 4 hours of septic shock onset to norepinephrine versus initial norepinephrine monotherapy in medically, critically ill patients with septic shock admitted from May 2014 to October 2015. Time to goal MAP was compared using Student t test and examined with Kaplan-Meier curves. Changes in Sequential Organ Failure Assessment (SOFA) scores were evaluated with Wilcoxon rank sum test. Results: Each group contained 48 patients. Mean arterial pressure (61.5 vs 58.6 mm Hg) and intravenous fluid volume received at vasopressor initiation (14.3 vs 25.2 hours, P = .014) were similar. Patients started on early vasopressin achieved and maintained goal MAP sooner (6.2 vs 9.9 hours, P = .023), experienced greater reductions in SOFA scores at 72 hours (−4 vs −1, P = .012), and had shorter hospital durations (343 vs 604 hours, P = .014). Not initiating early vasopressin trended toward an association with increased time to goal MAP ( P = .067). Conclusion: Early initiation of vasopressin in patients with septic shock may achieve and maintain goal MAP sooner and resolve organ dysfunction at 72 hours more effectively than later or no initiation.